TINGKAT PENDAPATAN ANGGOTA LMDH â€œLANCAR JAYAâ€ DARI SEKTOR PERTANIAN HORTIKULTURA DI DESA NGANCAR KECAMATAN NGANCAR KABUPATEN KEDIRI - Saputra, Erda Risky; Muttaqin, Tatag; Waskitho, Nugroho Tri (Universitas Muhammadiyah Malang, 2019)
AbstractionÂ Â Â Â Â Â This research was conducted on 10 November 2018 - 31 January 2019 in Ngancar Village, Ngancar District, Kediri Regency. The study was intended to determine the level of income of LMDH